PROFIL BISEKSUAL DI KOTA PEKANBARU - Cynthia Siregar; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Bisexual is adeviant sexual behavior. This sex has done by man to man and man to woman at once. The man is called gay and the woman is lesbian. This sexual orientation is very risky sexual behaviors that causes HIV/AIDS. This researchaims to find out the causes of what makes someone become bisexual and their relationships with families, couples and society. There is four informant in this research the informants, they have various experience inprocess of becoming bisexual. The research data were collected by interview, observation and documentation. The interview were used is a structured interview where the researchers first preparing a guidance interview. According to previous research it can be concluded that th bisexual is deviant sexual behavior. The entire informants is from the outside of Pekanbaru and have long settled in Pekanbaru. Their backgrounds were being a bisexual is because of the encouragement of psychological, sexual harassment, family and environmental influences. They have very good relationship with families, couples and society. Yettend to be introverted to the public because bisexual behavioris not appropriate with norms society.Keywords: bisexual, deviant sexual behavior.